Knowledgepoint : a study on the usability of the user interface for FTMSK'S knowledge portal / Sharliza Kamarulzaman - Kamarulzaman, Sharliza (2005)
To build a successfiil web portal, it is not only to have a great functioning of system, but a well designed and usable of user interfaces also needed. User interface is act like a medium while user interacts with portal. In case of that, a good design of user interface is required to make user feel comfortable and enjoy while using the portal. Ease of use makes the portal a place user wants to go. Knowledgepoint is also a web portal that comprises of three different frameworks which is OpenACS, uPortal, and e-Portfolio. Each of these frameworks has different interfaces from each other and needs to be redesigned and standardized. In the process of design and standardize the Knowledgepoint's interfaces, the usability aspects or factors need to be considered and applied. Observation on the user interface of portals for foreign universities which some of it used the same framework through internet has done in order to get information about how usable the interfaces are and the information then was used to be applied while designing Knowledgepoint's interfaces. Questionnaires also used to have a user perception on the Knowledgepoint's interfaces through the usability testing conducted. This research will use the information gathered to come out with a usable web portal interface.